Peningkatan Pengetahuan Petani dalam Budidaya Kakao Melalui Kegiatan Sekolah Lapang di Desa Bulili, Kabupaten Sigi - Rifana Rizki Maulida Ummah; Sri Widayanti (Institut Pertanian Bogor, 2025)
Farmer knowledge is an important factor in obtaining maximum cocoa production results. However, the majority of cocoa farmers in Bulili Village have limited knowledge of proper cultivation procedures in accordance with the Good Agricultural Practice (GAP). The cocoa farms in Bulili Village mostly have old cocoa plants and lack maintenance, which can impact the reduction in production yields. Maximum cocoa production can be achieved if farmers take good care of their crops. To achieve this, we aim to increase the knowledge of cocoa farmers in Bulili Village regarding proper cultivation procedures so that they can increase their production yields. This PKM (Community Service) activity was carried out using the Participatory Action Research (PAR) approach. The target of this activity was 15 cocoa farmers from Bulili Village who did not apply GAP. The results of the activity evaluation showed that the participants’ knowledge increased. Based on the results of the pre- and post-tests, there was an increase in the percentage of farmers with a good level of knowledge. The percentage increase in the number of farmers with a good level of knowledge of the field school activities on crop rehabilitation was 33%, in the GAP field school 47%, pest control 67%, liquid organic fertilizer 60%, and harvest and post-harvest 20%. In addition, the impact of increased knowledge has increased cocoa bean production to an average of 473.2 kg/ha/year from 395.6 kg/ha/year.